1999
DOI: 10.1046/j.1464-5491.1999.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based genetic screening for the estimation of Type 1 diabetes mellitus risk in Finland: selective genotyping of markers in the HLA‐DQB1, HLA‐DQA1 and HLA‐DRB1 loci

Abstract: The described strategy for genetic prediction of Type 1 diabetes mellitus relies on the convenient genotyping procedure and could be applied in large scale screening projects such as DIPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
1
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 27 publications
4
117
1
4
Order By: Relevance
“…The selection criteria for the study cohort comprising ICA-positive children limited our possibilities to analyse thoroughly the HLA effects, since most study subjects carried the DR4-DQB1*0302 haplotype, however, the contribution of the insulin and CTLA4 loci to the diseasespecific autoimmune phenomena could be fully explored. We also analysed the effect of DRB1*04 alleles on the DR4-DQB1*0302 haplotypes, since they confer different degrees of disease susceptibility in the Finnish population, as the DRB1*0401 allele is associated with higher risk than the DRB1*0404 variant and the DRB1*0403 allele is protective [28,35]. At the INS locus the −23 HphI polymorphism was used as genetic risk marker, where the A alleles are in strong linkage disequilibrium with the 5′ INS VNTR class I susceptibility variants and the T alleles are linked with the protective class III alleles [12,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection criteria for the study cohort comprising ICA-positive children limited our possibilities to analyse thoroughly the HLA effects, since most study subjects carried the DR4-DQB1*0302 haplotype, however, the contribution of the insulin and CTLA4 loci to the diseasespecific autoimmune phenomena could be fully explored. We also analysed the effect of DRB1*04 alleles on the DR4-DQB1*0302 haplotypes, since they confer different degrees of disease susceptibility in the Finnish population, as the DRB1*0401 allele is associated with higher risk than the DRB1*0404 variant and the DRB1*0403 allele is protective [28,35]. At the INS locus the −23 HphI polymorphism was used as genetic risk marker, where the A alleles are in strong linkage disequilibrium with the 5′ INS VNTR class I susceptibility variants and the T alleles are linked with the protective class III alleles [12,21].…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping The methods and the resolutions for the HLA DQB1 'full house' for the DQA1 and DRB1*04 typing were described earlier [27][28][29]. The INS −23 HphI and the CTLA4+49 polymorphisms were analysed using PCR and a lanthanide-labelled oligonucleotide hybridisation method [27,30].…”
Section: Methodsmentioning
confidence: 99%
“…In Caucasians, islet autoimmunity and type 1 diabetes are strongly associated with HLA DR3-DQ2 and DR4-DQ8 haplotypes (23), and recent studies from different European countries have confirmed that the HLA DR3-DQ2/DR4-DQ8 genotype is associated with the highest diabetes risk (29 -34). This genotype is found in 20 -30% of type 1 diabetic patients and in almost 50% of patients diagnosed in early childhood (23,(31)(32)(33)(34). Islet autoantibodies differ in their association with HLA haplotypes.…”
Section: Factors Influencing the Development Of Islet Autoimmunitymentioning
confidence: 99%
“…Three nonsynonymous SNPs were located in exon 9 [rs712701 (P321H), rs2233583 (V330A), and rs2233584 (Ter333W)], whereas the rs2233578 SNP (R133W) was in exon 3. HLA typing was performed in all Finnish subjects using methods described earlier (12,13). The INS Ϫ23 HphI SNP was typed with a similar oligonucleotide hybridization format (T probe 5Ј-Europium-CTGTCTCCCAGA-3Ј; A probe 5Ј-Terbium-CTG TCACCCAGA-3Ј).…”
Section: Hungarian Population Seriesmentioning
confidence: 99%